Research in Youth Culture and Policy: Current Conditions and Future Directions - Nadine Dolby (Social Work & Society, 2008)
Doria, the fictional main character in Faiza Guène's (2006/2004) acclaimed novel, Kiffe Kiffe Tomorrow, is an immigrant teenager growing up in the Paris projects. In the novel, Doria struggles to find her place in a society which seems to offer little hope for the future of the poor, black immigrants whose presence in France defines the postcolonial moment (Dimitriadis and McCarthy 2001). While Doria's parents and those of her friends and classmates long for home, Doria and her generation know only France, despite the difficulties and hardships life there presents. For them, there is only forward movement into a decidedly hybrid future, one in which their identities are in perpetual translation, as they negotiate constantly changing temporal and spatial registers (Hall 2002). In the U.S. context, JoAnn D'Alisera reflects on her study of Sierra Leonean communities in the Washington, D.C. area, as she writes, "These children, for their part, often describe themselves as simultaneously Sierra Leonean, Muslim, and American. In naming themselves, they more comfortably blur boundaries that their parents struggle to maintain in their own and in their children's lives" (p.126).